Guest Editorial Introduction to the Special Section on M-Health Beyond Seamless Mobility and Global Wireless Health-Care Connectivity. - Istepanian, R.S.H (IEEE Transactions on information technology in biomedicine)
M-Health can be defined as ?mobile computing, medical sensor, and communications technologies for health-care.? This emerging concept represents the evolution of e-health systems from traditional desktop ?telemedicine? platforms to wireless and mobile configurations. Current and emerging developments in wireless communications integrated with developments in pervasive and wearable technologies will have a radical impact on future health-care delivery systems. This editorial paper presents a snapshot of recent developments in these areas and addresses some of the challenges and future implementation issues from the m-Health perspective. The contributions presented in this special section represent some of these recent developments and illustrate the multidisciplinary nature of this important and emerging concept.